Determinants Of Food Choices on The Nutritional Status Of Adolescents In Merauke - Muktamar Umakaapa; Pricilya Margaretha Warwuru; Ade Yuni Sahruni; Febry Ramdhani Suradji; My Ismail (Jurnal Ners, 2025)
The issue of food selection or food choice among adolescents who often neglect health considerations has become one of the main public health concerns today. This pattern of food choice behavior among adolescents has significantly contributed to various health problems. This study aims to analyze the factors influencing food choices and their relationship with the nutritional status of adolescents in Merauke City. The factors examined in this study include health aspects, sensory appeal, price, convenience, and adolescents’ familiarity with the food. The research employed a cross-sectional design. Data were collected through questionnaires and nutritional status measurements of 56 respondents based on Body Mass Index (BMI). Data analysis was conducted using the Statistical Package for Social Sciences (SPSS) software, with both univariate and bivariate analyses. The results show that health-related reasons are weakly correlated with adolescents’ nutritional status. Sensory appeal is moderately correlated with nutritional status. There is no relationship between price and nutritional status. Convenience is weakly correlated with nutritional status. Familiarity with food shows a strong correlation with adolescents’ nutritional status. This study concludes that the factor most strongly associated with the nutritional status of adolescents in Merauke is food selection based on their familiarity with certain types of food.